Cerium oxide for L-band Q-switched pulse laser generation - Mansor, M.; Zainol Abidin, N.H.; Ng, E.K.; Garg, A.K.; Liew, J.Y.C.; Alresheedi, M.T.; Mahdi, M.A. (Academic Press, 2024)
Cerium oxide (CeO2), a rare earth metal oxide belonging to the lanthanide group is a mature engineered nanoparticle that has been developed for various industry applications. The nanoparticle features defects in its lattice structure, which is highly advantageous for bandgap tuning, and is acclaimed for its least cytotoxicity among other metal oxides. In this work, CeO2 is employed as a saturable absorber (CeO2-SA) in the generation of an L-band Q-switched erbium-doped fiber laser. Q-switching was attained at 33.33 mW pump power threshold with a central wavelength of 1600.512 nm. Within 33.33 mW to 153.20 mW pump power range, the Q-switched laser obtained pulse repetition rates between 11.00 to 34.48 kHz, and pulse widths between 39.0 to 12.0 µs, with a high maximum pulse energy of 410 nJ. The Q-switched fiber laser remained stable over a 45-minute observation time at 153.20 mW pump power. The room temperature and direct mechanical deposition fabrication technique of the CeO2-SA in this work demonstrates the extreme simplicity and low cost of the device, which would reduce the overall cost and facilitate a wider technology adoption of pulse laser systems. © 2024 Elsevier Inc.